بلوچستان ءِ تاریخ نوکیں سنگ ءِ دورتاں رود ءِ دور: History of Balochistan: Modern stone age to early iron age - Baloch, Tahir (Hanken, 2009)
The human civilization is no t new but consist of a long history from the beginning of the first day. Development s and declination s come and go by the sphere of time but leave some effect in the human history. This paper will focus the ancient civilization of Mehragarh and the archaeological sites of Balochistan such as, Killi Gul Muhammad, Anjeera, Nal Shahi, Mustang and Bostan. The proto - historic, pre historic, chalcolithic, Mesolithic and neo lithic period of Balochistan will be discussed.